Legal regime of lobby activities. A comparative view - Ovidiu-Horia MAICAN (Juridical Tribune, 2014)
A very important aspect is that countries with specific rules and regulations regulating the activities of lobbyists and interest groups are more the exception than the rule. The interest groups are pursuing their goals in the political arena by lobbying, or attempting to influence policy-making, are consistent with the spirit of democracy. In practice, interest group influence can sometimes lead to political corruption, the inequality of representation, and the overcrowding of political institutions. As a consequence, some political systems find it appropriate to regulate interest representation.